Предмет: Алгебра,
автор: Аноним
(с+3/с-3 - с/с+3)*с-3/с+1
Ответы
Автор ответа:
1
1) ( С +3 ) \ ( С - 3) - С \ ( С + 3 ) = [ ( С + 3)^2 - C*( C - 3 ) ] \ C^2 - 9 =
= ( C^2 + 6C + 9 - C^2 + 3C ) \ C^2 - 9 = 9C + 9 \ C^2 - 9 = 9 *( C + 1 ) \ C^2 - 9
2) 9 * ( C + 1 ) \ (C -3)*(C + 3 ) * ( C - 3 ) \ (C + 1) = 1 \ ( C + 3 )
Ответ 1 \ ( С + 3 )
= ( C^2 + 6C + 9 - C^2 + 3C ) \ C^2 - 9 = 9C + 9 \ C^2 - 9 = 9 *( C + 1 ) \ C^2 - 9
2) 9 * ( C + 1 ) \ (C -3)*(C + 3 ) * ( C - 3 ) \ (C + 1) = 1 \ ( C + 3 )
Ответ 1 \ ( С + 3 )
Похожие вопросы
Предмет: Окружающий мир,
автор: laisat1
Предмет: Черчение,
автор: Vladosik159
Предмет: Русский язык,
автор: diana200719860
Предмет: Английский язык,
автор: lololol7530
Предмет: Биология,
автор: denisUkraine